2016
DOI: 10.1016/j.atherosclerosis.2016.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgE levels in coronary artery disease

Abstract: The development and progression of atherosclerosis and its predisposition for unstable angina, myocardial infarction and stroke is associated with traditional risk factors such as family history, cigarette smoking, hypertension, dyslipidemia, diabetes mellitus, obesity, imbalance of the hemostatic/fibrinolytic system and sedentary lifestyle. However, much of the variability in atherosclerosis and its manifestations still remains unexplained. Nowadays, there is increasing evidence that immunologic mechanisms pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 14 publications
0
26
1
Order By: Relevance
“…IgE is a surface‐protective antibody, which is closely related to allergic reactions, such as asthma. Previous studies have indicated that IgE participates in the etiopathogenesis of cardiovascular disease . In our research, although a high level of serum IgE was found in the NAFLD participants, no significant relationship between NAFLD and IgE was detected after adjusted for confounding factors.…”
Section: Discussioncontrasting
confidence: 74%
“…IgE is a surface‐protective antibody, which is closely related to allergic reactions, such as asthma. Previous studies have indicated that IgE participates in the etiopathogenesis of cardiovascular disease . In our research, although a high level of serum IgE was found in the NAFLD participants, no significant relationship between NAFLD and IgE was detected after adjusted for confounding factors.…”
Section: Discussioncontrasting
confidence: 74%
“… 1 3 Recent reports have confirmed a role for mast cells and demonstrated an association between levels of total serum IgE and cardiovascular disease, though no specific allergens have been identified. 4 6 Galactose-α-1,3-galactose (α-Gal) is a blood group-like oligosaccharide of nonprimate mammals and is recognized in humans as a target of natural IgM, IgA, and IgG antibodies. 7 , 8 In 2008, IgE specific to α-Gal was identified as the cause of anaphylactic reactions to cetuximab.…”
mentioning
confidence: 99%
“…Khamis et al () recently found total IgG levels correlated with CVD and adjusting for total levels negated the correlation of oxLDL‐specific IgG. Increased serum IgE levels have been associated with enhanced risk of CAD, and in particular plaque stability (Kounis and Hahalis, ). In addition, IgE, eosinophil and mast cell responses occur as part of immune responses in ACSs (Kritikou et al, ).…”
Section: Atherosclerosis and The Adaptive Immune System In Patientsmentioning
confidence: 99%